Evaluation of Natural and Botanical Medicines for Activity Against Growing and Non-growing Forms of B. burgdorferi - Feng, Jie; Leone, Jacob; Schweig, Sunjya; Zhang, Ying (Frontiers in Medicine, 2020)
Lyme disease is the most common vector-borne disease in the US and Europe. Although the current recommended Lyme antibiotic treatment is effective for the majority of Lyme disease patients, about 10-20% patients continue to suffer from persisting symptoms. There have been various anecdotal reports on the use of herbal extracts for treating patients with persisting symptoms with varying degree of improvements. However, it is unclear whether the effect of the herb products is due to their direct antimicrobial activity or their effect on host immune system. In the present study, we investigated the antimicrobial effects of 12 commonly used botanical medicines and three other natural antimicrobial agents for potential anti-Borrelia burgdorferi activity in vitro. Among them, 7 natural product extracts at 1% were found to have good activity against the stationary phase B. burgdorferi culture compared to the control antibiotics doxycycline and cefuroxime. These active botanicals include Cryptolepis sanguinolenta, Juglans nigra (Black walnut), Polygonum cuspidatum (Japanese knotweed), Artemisia annua (Sweet wormwood), Uncaria tomentosa (Cat's claw), Cistus incanus, and Scutellaria baicalensis (Chinese skullcap). In contrast, Stevia rebaudiana, Andrographis paniculata, Grapefruit seed extract, colloidal silver, monolaurin, and antimicrobial peptide LL37 had little or no activity against stationary phase B. burgdorferi. The minimum inhibitory concentration (MIC) values of Artemisia annua, Juglans nigra, and Uncaria tomentosa were quite high for growing B. burgdorferi, despite their strong activity against the non-growing stationary phase B. burgdorferi. On the other hand, the top two active herbs, Cryptolepis sanguinolenta and Polygonum cuspidatum, showed strong activity against both growing B. burgdorferi (MIC=0.03%-0.06% and 0.25%-0.5% respectively) and non-growing stationary phase B. burgdorferi. In subculture studies, only 1% Cryptolepis sanguinolenta extract caused complete eradication, while doxycycline and cefuroxime and other active herbs could not eradicate B. burgdorferi stationary phase cells as many spirochetes were visible after 21-day subculture. Further studies are needed to identify the active constituents of the effective botanicals and evaluate their combinations for more effective eradication of B. burgdorferi in vitro and in vivo. The implications of these findings for improving treatment of persistent Lyme disease are discussed.